Media Rich PDF Publishing: Bridging the Gap Between Traditional Print and Multimedia Publishing. - Lisi, Jason (International Journal of the Book, 2010)
Traditional print publishing has seen a decline in recent years, partly due to new forms of multimedia publication. Typically there is a clear distinction between print and multimedia publication, and often these two forms of publishing are designed and created separately from one another. Media Rich PDF publishing is a unique form of media convergence that allows designers to blend the superior image clarity and typographical power of printed documents with the interactivity and media flexibility of multimedia publishing. Through media rich PDFs, authors can create high quality printable documents that remain economical in file size, allowing them to be disseminated electronically through email or websites. Media rich PDFs are platform independent, easily managed by inexperienced users, and easy to create. One significant advantage of media rich PDFs is that one file can be created and used to create traditional commercial print products as well as an electronic multimedia experience. This can save publishers significant time and money when trying to publish across multiple mediums. This paper discusses the pros and cons of media rich PDF publishing as it relates to both traditional print publishing and multimedia applications. These arguments will form the basis for the argument that media rich PDFs can be used as a means of bridging two forms of information publishing that are traditionally considered to be incompatible.